Truncated mini LRP1 transports cargo from luminal to basolateral side across the blood brain barrier - Fritzen, Laura; Wienken, Katharina; Wagner, Lelia; Kurtyka, Magdalena; Vogel, Katharina; Körbelin, Jakob; Weggen, Sascha; Fricker, Gert; Pietrzik, Claus U. (Fluids and barriers of the CNS, 2024)
Background: The most crucial area to focus on when thinking of novel pathways for drug delivery into the CNS is the blood brain barrier (BBB). A number of nanoparticulate formulations have been shown in earlier research to target receptors at the BBB and transport therapeutics into the CNS. However, no mechanism for CNS entrance and movement throughout the CNS parenchyma has been proposed yet. Here, the truncated mini low-density lipoprotein receptor-related protein 1 mLRP1_DIV* was presented as blood to brain transport carrier, exemplified by antibodies and immunoliposomes using a systematic approach to screen the receptor and its ligands’ route across endothelial cells in vitro. Methods: The use of mLRP1_DIV* as liposomal carrier into the CNS was validated based on internalization and transport assays across an in vitro model of the BBB using hcMEC/D3 and bEnd.3 cells. Trafficking routes of mLRP1_DIV* and corresponding cargo across endothelial cells were analyzed using immunofluorescence. Modulation of γ-secretase activity by immunoliposomes loaded with the γ-secretase modulator BB25 was investigated in co-cultures of bEnd.3 mLRP1_DIV* cells and CHO cells overexpressing human amyloid precursor protein (APP) and presenilin 1 (PSEN1). Results: We showed that while expressed in vitro, mLRP1_DIV* transports both, antibodies and functionalized immunoliposomes from luminal to basolateral side across an in vitro model of the BBB, followed by their mLRP1_DIV* dependent release of the cargo. Importantly, functionalized liposomes loaded with the γ-secretase modulator BB25 were demonstrated to effectively reduce toxic Aß42 peptide levels after mLRP1_DIV* mediated transport across a co-cultured endothelial monolayer. Conclusion: Together, the data strongly suggest mLRP1_DIV* as a promising tool for drug delivery into the CNS, as it allows a straight transport of cargo from luminal to abluminal side across an endothelial monolayer and it’s release into brain parenchyma in vitro, where it exhibits its intended therapeutic effect.